(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2017)
The absolute superiority of the direct product of graphs is shown at both the upper and lower limits. The limits include the total number 2 for dominance, the total number 2 times for dominance and the factors’ number for open packing. Those relationships have an exact total number of supremacy. A set of graphs reveals that the limits are best feasible. The number of direct graphics products dominating. We show that the step domination number of any tree T satisfies where n is the number of vertices of T, an d D is its diameter. It is also proved that if some requirements are set ona tree T then,